Design and synthesis of Co–N–C porous catalyst derived from metal organic complexes for highly effective ORR. Issue 45 (27th October 2017) - Liu, Heng; Wang, Min-Qiang; Chen, Zhao-Yang; Chen, Hao; Xu, Mao-Wen; Bao, Shu-Juan
Abstract : In this work, a novel and slack rose-like metal organic precursor was designed and used for the preparation Co and N co-doping carbon materials. As the ORR catalysts, they delivered comparable electrochemical performance with Pt/C. Abstract : In this work, we reported a novel and slack rose-like metal organic precursor designed by coordinating p -phenylenediamine with cobalt ion. After subsequent pyrolysis and acid etching process, the as-prepared Co–N–C catalyst delivered a superior catalytic activity and long-term durability. Further applied in the Zn–air battery, it also displayed a comparable performance with 20% Pt/C.